2016
DOI: 10.18203/2320-6012.ijrms20163330
|View full text |Cite
|
Sign up to set email alerts
|

Can peripheral blood smear examination be totally replaced by automated hematology analyser - with special reference to anemia?

Abstract: INTRODUCTIONPeripheral blood smear (PBS) examination is a part of the routine work of every laboratory. The manual examination of these images is tedious, time consuming and suffers from interobserver variation. This has motivated researchers to develop different algorithms and methods to automate PBS image analysis. The automated hematology analyzers give more accurate and <1% coefficient of variation for the RBC indices and hence have replaced the manual methods. Thus we can definitely conclude that the hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
(4 reference statements)
5
3
1
Order By: Relevance
“…Out of the 1000 cases of anemia included in our study, we observed a higher prevalence in females, with 52.7% of the cases being female. This finding is consistent with past research conducted by Singhal et al 13 and Garg et al, 4 where they reported female predominance with 64.9% and 62.9% cases, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Out of the 1000 cases of anemia included in our study, we observed a higher prevalence in females, with 52.7% of the cases being female. This finding is consistent with past research conducted by Singhal et al 13 and Garg et al, 4 where they reported female predominance with 64.9% and 62.9% cases, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…12 Hence our study showed that PBF provided additional information in only 16% cases of anaemia. This was in concordance with the study conducted by Singal S et al 16 which showed that PBS examination provide additional information only in 11.4% cases of anaemia. Almost similar result was obtained by Froom P et al 17 as PBF provided additional information in 13.9% cases.…”
Section: Discussionsupporting
confidence: 93%
“…The total number of cases of anemia in our study was 1000. Female predominance was observed in the present study with 61% of the cases which was comparable to the past similar research of Singhal et al, (64.9%) 6 and Garg et al, (62.9%). 7…”
Section: Sex Distributionsupporting
confidence: 92%